2012
DOI: 10.5923/j.ajb.20120201.02
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of Metabolic Syndrome in Serum of Some Cigarette Smokers in Delta State, Nigeria

Abstract: Cigarette smoking could predispose an individual to a multitude of diseases which include metabolic syndrome. This study evaluates the biomarkers (blood glucose, body mass index [BMI], lipid profile and blood pressure) of metabolic syndrome in serum of some cigarette smokers in Delta State. One hundred apparently healthy male undergraduate students divided into two groups (50 smokers and 50 non-smokers) were recruited for the study conducted between August, 2010 and April 2011. Body mass index (BMI), blood glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 27 publications
3
4
0
Order By: Relevance
“…These results were also in agreement with the results of the researcher [14,15], which showed an increase in globulin level in smokers due to an increase in the synthesis of inflammatory cytokines, interleukins and C-reactive protein. Also indicated that the imbalance between low albumin and high Globulins in smokers compared to non-smokers causes serious diseases in the future "by increasing the smoking period for its effect on the concentration of total protein in the blood and thus its effect on body functions" [16,17,18].…”
Section: Resultssupporting
confidence: 93%
“…These results were also in agreement with the results of the researcher [14,15], which showed an increase in globulin level in smokers due to an increase in the synthesis of inflammatory cytokines, interleukins and C-reactive protein. Also indicated that the imbalance between low albumin and high Globulins in smokers compared to non-smokers causes serious diseases in the future "by increasing the smoking period for its effect on the concentration of total protein in the blood and thus its effect on body functions" [16,17,18].…”
Section: Resultssupporting
confidence: 93%
“…We assume that the different results from previous studies may be related to dosage or duration consumption of finasteride, age and nutritional status of patients and different genetic ability of drug hepatic metabolism. While HDL to LDL ratio has been proved to be a predictor factor of cardiovascular disease (Reaven., 1988;Onyesom et al, 2012), our study did not show significant change after 3 and 6 months but changes ratio between third and sixth month were significant.…”
Section: Discussionmentioning
confidence: 62%
“…Also, an inverse relationship exists between the plasma level of free testosterone and serum triglyceride (Hämäläinen et al, 1987). HDL to LDL ratio has been confirmed to be not only an important factor for development of cardiovascular disease (Reaven, 1988;Onyesom et al, 2012) but also used to efficacy of anti-lipid drug therapy (Kannel, 2005). …”
Section: Introductionmentioning
confidence: 99%
“…The present result is concurrence with results of other reviews (20-21). Another study found Glucose level for smokers was significantly lower than that of the non-smokers (22). In another hand, other studies revealed an increase in serum Glucose concentration (23,24,25).…”
Section: Discussionmentioning
confidence: 95%
“…There are reviews evaluations of a change of Red Blood Cells Parameters in smokers (16,17,18,19) and also the Glucose levels (20,21,22,23,24,25).However, the literature reporting the effects of Pack-Year of Cigarettes Smoking on Red Blood Cells Parameters and also Glucose levels is limited.…”
Section: Discussionmentioning
confidence: 99%